The Effect of Vacum and Nonvacum Packaging System on the Smoke Eel (Monopterus albus) added With Lemongrass (Cymbopagon citratus) Stored at Room Temperature (29 ± 3⁰C) - Arif Jaso Sajiwo; Dewita Buchari; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aimed to observe the different of vacum package system and nonvacum on the smoke eel (Monopterus albus) quality added with lemongrass stored at room temperature. The research method used was comparative experiment between vacum package and nonvacum package and the data collected were analyzed by using T test. Smoke eel evaluated with organoleptic, water content analysis, TBA and staphylococcus aurerus bacteria. The result showed that best organoleptic score appearance (2,33), aroma (2,25), texture (2,19) and taste (2,14) on vacum smoke eel which had lowest water content value ( 24,92%) and best TBA value (1,47%). Staphylococcus aurerus bacteria was not found on smoke eel.Keywords: Monopterus albus, nonvacum, smoke eel, vacum